Yield, nutrient status and biochemical properties of soil affected by integrated nutrient management in mango orchard - KUMAR, RAUSHAN; KUMAR, RAVINDRA; SUPRIYA; KUMARI, SUMAN; S., SUDARSHAN (Journal of Soil and Water Conservation, 2025)
The reckless use of chemical fertilizers has led to increase in yield of mango, but also negatively affected soil, water, fruits quality and human health. Keeping these points under consideration, the experiment was conducted on integrated plant nutrient management under the experimental area of BAU, Sabour, Bhagalpur (Bihar) for three consecutive seasons i.e., monsoon (2020), winter (2020) and monsoon (2021) during the year 2020 and 2021. Eight treatments were taken i.e., T1- [1000:500:500 g of NPK/tree/year (control /RDF)], T2- [T1 + Organic mulching 10 cm thick], T3- [½ RDF + 50 kg FYM + 25 g Trichoderma], T4- [½ RDF + 50 kg FYM + 250 g Azospirillum], T5- [ ½ RDF + 50 kg FYM + 250 g Azotobacter], T6-[½ RDF + 50 kg FYM + 5 kg Vermicompost], T7- [½ RDF + 50 kg FYM + 250 g Pseudomonas fluorescens] and T8-[½ RDF + 50 kg FYM + 250 g Trichoderma + 250 g Pseudomonas fluorescens] with three replications in Randomized block design. Treatment T4 performed better in respect to the maximum number of 590 fruits/tree and yields of 174.91 kg/tree. The maximum N, P and K content in leaf was obtained to the tune of 1.81% (T4), 0.14 (T6), 1.20% (T4), respectively. Available N, P and K of 188.16 (T4), 52.25 (T6) 534.60 (T6) kg ha-1, respectively and dehydrogenase enzymes activity of 57.30 μg TPF g-1 soil 24h-1 (T4) has significantly improved. Thus, the application of treatment T4 (½ RDF + 50 kg FYM + 250 g Azospirillum) followed by T6 (½ RDF + 50 kg FYM + 5 kg Vermicompost) played an indispensable role in increasing the yield, nutrients and biochemical properties of soil of the mango orchard.